Análise da distribuição do Tityus serrulatus no município de Santa Gertrudes-SP - Baldin, Liliane Gabriele [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Scorpionism in Brazil has shown high rates of occurrence in recent years and is considered a public health issue. The main cause of accidents is Tityus serrulatus (yellow scorpion), a parthenogenetic, opportunistic animal, adapted to an anthropized environment and, therefore, easily dispersed and established in an urban environment. In the municipality of Santa Gertrudes - SP, there was an increase in the number of notifications of these animals in homes, leadin to the proposition of the "Projeto Aracnídeos", which carried out weekly searches and guidance to the population in order to avoid accidents and control the population of the species.The objective of the work was to analyze the distribution of this scorpion in the city of Santa Gertrudes-SP, identifying if there were concentration points of this event in the period 2017-2020 and to study the modification of these areas in the period. For this, the data on notifications of notifications and accidents were collected through the Epidemiological Surveillance of the municipality and the data on captures through the Project. There was a preparation of maps containing the points of occurrence of notifications and captures in each neighborhood annually. Statistical analysis of “Pearson” and “Spearman” correlations between capture and notification data, and with the mean temperature indices and mean precipitation of data from all years were also carried out in order to determine the relationship between them. To identify the changes that occurred over the years and in the areas studied, the hypothesis tests “Kruskal-Walis”, “Dunn's pot hoc” and “ANOVA” were used. This study identifies the areas of positive and high captures and notifications. It was also possible to verify that the Central region is the place where these animals are most distributed and that there were differences between the areas notified in the study period, but not between the capture areas. It was also possible to identify that there was no variation in the amount of occurrence in the years studied.

O escorpionismo no Brasil apresentou altos índices de ocorrência nos últimos anos e é considerado um problema de saúde pública. O principal causador de acidentes é a espécie Tityus serrulatus (escorpião amarelo), um animal partenogenético, oportunista, adaptado ao ambiente antropizado e dessa forma, apresenta fácil dispersão e estabelecimento em ambiente urbano. No munícipio de Santa Gertrudes - SP, foi observado um aumento na quantidade de avistamento desses animais nas residências, sendo necessária a criação do “Projeto Aracnídeos”, que realizava buscas semanais e orientações à população a fim de evitar acidentes e controlar a população da espécie. O objetivo deste trabalho foi a análise da distribuição da ocorrência do escorpião amarelo no município de Santa Gertrudes-SP, identificando se houve pontos de concentração desse evento no período de 2017 a 2020 e estudo da modificação dessas áreas no período. Para isso, os dados de notificações de avistamentos e acidentes foram obtidos por meio da Vigilância Epidemiológica do município e os dados das capturas por meio do Projeto. Houve a confecção de mapas contendo os pontos de ocorrência de notificações e de capturas em cada bairro anualmente. Foram realizadas também análises estatísticas de correlação de “Pearson” e “Spearman” entre os dados de captura e notificações, e com os índices de temperatura média e pluviosidade média mensais de todos os anos, a fim de determinar a relação entre eles. Para identificação das mudanças ocorridas ao longo dos anos e nas áreas estudadas os testes de hipóteses “Kruskal-Walis”, “Dunn’s pot hoc” e “ANOVA” foram utilizados. Este estudo identificou que as áreas de capturas e notificações apresentam alta correlação positiva. Foi possível verificar também que a região do Centro é o local onde apresenta maior ocorrência desses animais e que houve diferenças significativas entre as áreas notificadas no período estudado, mas não entre as áreas de capturas. Foi possível identificar também que não houve uma variação significativa da quantidade de ocorrência nos anos estudados
Analysis of the distribution of Tityus serrulatus in the county of Santa Gertrudes-SP
Keywords: Yellow scorpion; Public health; Tityus serrulatus; Escorpião amarelo; Santa Gertrudes; Saúde pública